2018
DOI: 10.17576/jkmjc-2018-3401-01
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Marketing Communication and Consumer-Based Brand Equity: An Account of Automotive Brands in Malaysia

Abstract: Achieving brand equity are top priorities for many organizations because brand is one of the most prized assets of any organization. As such, the academia continues to exert considerable efforts on understanding the factors that influence the development of brand equity. For instance, previous studies have demonstrated that social media communication has significant impact on Consumer-Based Brand Equity (CBBE), however, researchers have not really focused on the relationships of several types of marketing comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
0
20
0
4
Order By: Relevance
“…It encourages ones to realize their buying intentions into purchase decisions. In line with this statement, Adetunji et al (2018) argue that interactive marketing allows marketers to gain interactive relationships with their consumers and brands. In other words, besides as an independent variable, interactive marketing likely moderates the association between intention to buy and purchase decisions by convincing consumers to buy products or brands.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It encourages ones to realize their buying intentions into purchase decisions. In line with this statement, Adetunji et al (2018) argue that interactive marketing allows marketers to gain interactive relationships with their consumers and brands. In other words, besides as an independent variable, interactive marketing likely moderates the association between intention to buy and purchase decisions by convincing consumers to buy products or brands.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, interactive marketing also connects consumers with brands (Adetunji et al, 2018) or products. Hence, it is also arguably a moderating variable that affects purchase decision processes.…”
Section: Interactive Marketing As a Moderator Variable Between Intentmentioning
confidence: 99%
See 1 more Smart Citation
“…Online marketing is also understood as e-marketing, where it markets products and services over the internet (Chien and Lee, 2018). Previous studies suggested that the applications of online marketing consisted but not limited to search engine optimization, e-mail marketing, and social media marketing (Adetunji et al, 2018;Giomelakis and Veglis, 2016;Karjaluoto and Taiminen, 2015). Nevertheless, online marketing, such as affiliate marketing, has not received enough attention in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the automobile industry has witnessed a shift of power from the west to east (Bernhart, Kleimann, & Hoffmann, 2011) as many countries in Asia have become major automobile manufacturers as well as these countries have a substantial share in the aggregate demand of the automobile market. The growing demand for automobiles in Asia has also identified the importance of leveraging customer-based brand equity (CBBE) amidst the burgeoning pressure on the automobile manufacturers due to increasing competition in the automobile industry (Adetunji, Rashid, & Ishak, 2018). The mounting competitive pressures on the automobile brands in Asian markets have also identified the falling retention rate of automobile customers due to various factors such as preference for higher product quality expectations, better customer experience and due to social factors like growing desire for automobile brands that raise the self-image of customers and help them look distinctive (Edmunds, 2018;Gerrits, Zhang, Klotz, Xu, & Xie, 2014).…”
Section: Introductionmentioning
confidence: 99%